Effects of supplemental oxygen therapy in patients with suspected acute myocardial infarction: a meta-analysis of randomised clinical trials. Issue 20 (29th March 2018) - Sepehrvand, Nariman; James, Stefan K; Stub, Dion; Khoshnood, Ardavan; Ezekowitz, Justin A; Hofmann, Robin
Abstract : Background: Although oxygen therapy has been used for over a century in the management of patients with suspected acute myocardial infarction (AMI), recent studies have raised concerns around the efficacy and safety of supplemental oxygen in normoxaemic patients. Objective: To synthesise the evidence from randomised controlled trials (RCTs) that investigated the effects of supplemental oxygen therapy compared with room air in patients with suspected or confirmed AMI. Methods: For this aggregate data meta-analysis, multiple databases were searched from inception to 30 September 2017. RCTs with any length of follow-up and any outcome measure were included if they studied the use of supplemental O2 therapy administered by any device at normal pressure compared with room air. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, an investigator assessed all the included studies and extracted the data. Outcomes of interests included mortality, troponin levels, infarct size, pain and hypoxaemia. Results: Eight RCTs with a total of 7998 participants (3982 and 4002 patients in O2 and air groups, respectively) were identified and pooled. In-hospital and 30-day death occurred in 135 and 149 patients, respectively. Oxygen therapy did not reduce the risk of in-hospital (OR, 1.11 (95% CI 0.69 to 1.77)) or 30-day mortality (OR, 1.09 (95% CI 0.80 to 1.50)) in patients with suspected AMI, and the results remained similar in the subgroup of patients with confirmed AMI. The infarct size (based on cardiac MRI) in a subgroup of patients was not different between groups with and without O2 therapy. O2 therapy reduced the risk of hypoxaemia (OR, 0.29 (95% CI 0.17 to 0.47)). Conclusion: Although supplemental O2 therapy is commonly used, it was not associated with important clinical benefits. These findings from eight RCTs support departing from the usual practice of administering oxygen in normoxaemic patients.